Early initiation of renal replacement treatment in patients with acute kidney injury: A systematic review and meta-analysis. Issue 46 (November 2016) - Wang, Hongwei; Li, Liwei; Chu, Qinjun; Wang, Yong; Li, Zhisong; Zhang, Wei; Li, Lanlan; He, Long; Ai, Yanqiu
Abstract: Background: Acute kidney injury (AKI) is associated with a substantially increased risk of mortality for many hospitalized patients. It has been suggested that early initiation of renal replacement treatment has a favorable outcome in critically ill patients complicated with AKI. However, results of studies evaluating the effect of early initiation strategy of renal replacement treatment on AKI have been controversial and contradictory. The aim of this meta-analysis is to examine the effect of early initiation of renal replacement treatment on patients with AKI. Methods: The authors searched relevant studies in PubMed, EMBASE, and the Cochrane Library through August 2016. We searched for all eligible randomized controlled trials with regard to the role of early initiation of renal replacement treatment in mortality among patients with AKI. We extracted the following information from each study: mortality, length of stay in intensive care unit (ICU), and length of stay in hospital. Random and fixed effect models were used for pooling data. Results: Twelve trials including 1756 patients were included. The results of this meta-analysis showed that there was no significant difference between the mortality of early and delayed strategy for the initiation of renal replacement treatment using the random effect model (odds ratio = 0.78; 95% confidence interval [CI], 0.52–1.19; P  = 0.25), with wild heterogeneity (chi 2  = 33.50; I 2  = 67%). Analyses from subgroup sepsis and postsurgery came to similar results. In addition, compared with delayed initiation strategy, early initiation showed no significant advantage in length of stay in ICU (mean difference = −0.80; 95% CI, −2.59 to 0.99; P  = 0.56) and length of stay in hospital (mean difference = −7.69; 95% CI, −16.14 to 0.76; P  = 0.07). Conclusion: According to the results from present meta-analysis, early initiation of renal replacement treatment showed no survival benefits in patients with AKI. To achieve optimal timing of renal replacement treatment, further large multicenter randomized trials, with widely accepted and standardized definition of early initiation, are still needed.